The Poppy Lady : Moina Belle Michael and her tribute to veterans - Walsh, Barbara Elizabeth (Calkins Creek, 2012)
Known as the Poppy Lady, Moina Belle Michael, a schoolteacher from Georgia, successfully established the Flanders Field Memorial Poppy as a universal symbol of tribute and support for veterans and their families during World War I and II.